1993
DOI: 10.21273/jashs.118.5.623
|View full text |Cite
|
Sign up to set email alerts
|

Firmness and Decay of Apples following Postharvest Pressure Infiltration of Calcium and Heat Treatment

Abstract: Heating `Golden Delicious' apples (Malus domestica Borkh.) for 4 days at 38C or pressure-infiltrating them with a 4% CaCl2 solution reduced decay and maintained fruit firmness during 6 months of storage at 0C. Heating reduced decay caused by Penicillium expansum Link ex Thorn by ≈30%, while pressure infiltration with CaCl2 reduced decay by >60%. Pressure infiltration with CaCl2 after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(36 citation statements)
references
References 19 publications
4
32
0
Order By: Relevance
“…However, cultivars with a high tolerance to storage diseases thus appear to have not only above-average firmness at harvest but also less softening during storage. The positive effect of higher firmness (due to calcium infiltration) on fungal decay has already been well studied, indicating that improvement of fruit firmness can improve storability in several ways (Conway et al, 1991;Sams et al, 1993).…”
Section: Importance Of Harvest Date Fruit Firmness and Softeningmentioning
confidence: 99%
See 1 more Smart Citation
“…However, cultivars with a high tolerance to storage diseases thus appear to have not only above-average firmness at harvest but also less softening during storage. The positive effect of higher firmness (due to calcium infiltration) on fungal decay has already been well studied, indicating that improvement of fruit firmness can improve storability in several ways (Conway et al, 1991;Sams et al, 1993).…”
Section: Importance Of Harvest Date Fruit Firmness and Softeningmentioning
confidence: 99%
“…So far, no major genes providing resistance against the storage diseases have been identified but quantitatively inherited traits associated with chemical contents, fruit texture, structure of the fruit epidermis and ripening behavior may affect the ability of different cultivars to withstand fungal attacks (Prusky et al, 2004;Blazek et al, 2007;Nybom et al, 2008;Johnston et al, 2009). Positive effects of increased firmness and less softening due to calcium spraying, have been documented in a series of pre-and postharvest treatments of apple fruit, indicating that fungal decay caused by P. expansum, Botrytis cinerea and Glomerella cingulata can be significantly reduced (Conway et al, 1991;Sams et al, 1993;Conway et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Calcium is most frequently associated with stress tolerance, fruit firmness, ripening and senescence (Shear , Poovaiah , Martin‐Diana et al ). Pre‐ and Postharvest calcium treatments maintain fruit firmness and prevent decay in both climacteric and nonclimacteric fruits (Poovaiah and Shekhar , Conway and Sams , Abbott et al , Sams et al , Saftner et al , Saftner et al , Park et al , Ritenour et al ). Calcium is directly and integrally involved in texture changes and in maintaining fruit quality (Raese and Drake , Raese and Drake ).…”
Section: Introductionmentioning
confidence: 99%
“…A synergistic effect was observed when heated fruit were dipped in CaCl 2 solutions prior to storage (Klein & Lurie, 1994). Sams et al (1993) reported that heating 'Golden Delicious' apples for 4 days at 388C and then infiltrating them with calcium reduced decay caused by P. expansum by 30% and maintained fruit firmness during 6 months storage at 08C. The response of apples to heat treatments may vary according to cultivar, as 'Golden Delicious' and 'Delicious' showed relatively strong tolerance heat (Kim et al, 1993).…”
Section: Introductionmentioning
confidence: 99%